Impact of a nurse-led feeding protocol in a pediatric intensive care unit. (March 2016) - Ang, Bixia; Han, Wee Meng; Wong, Judith Ju-Ming; Lee, Ang Noi; Chan, Yoke Hwee; Lee, Jan Hau
Background: To determine effectiveness of a nurse-led, volume-based feeding protocol in our pediatric intensive care unit (PICU), we evaluated patients' nutrition adequacy pre- and post-protocol implementation. Methods: We conducted an observational study of patients admitted for more than three days in the PICU during pre- and post-feeding protocol periods. We recorded energy and protein intake and feed interruptions in patients started on enteral nutrition over the first seven days of admission. We excluded patients with septic shock requiring more than two inotropes, post-cardiac and post-gastrointestinal surgeries. To determine nutrition adequacy, actual energy and protein intakes were compared with calculated requirements, expressed as percentages. Results: We had a total of 40 patients (20 in the pre- and post-protocol groups, respectively) with median age of 9.4 (interquartile range (IQR) 2.8, 57) months. Median time to feed initiation was similar between groups (20.0 (IQR 17.0, 37.5) vs. 21.5 (IQR 10.5, 27.0) hours, p = 0.516). There was no difference in median energy (55 (IQR 12, 102) vs. 59 (IQR 25, 85) %, p = 0.645) and protein intake (53 (IQR 16, 124) vs. 73 (IQR 22, 137) %, p = 0.069) over the seven-day period between groups; the proportion of patients meeting their energy (10 vs. 35%, p = 0.127) and protein goal (15 vs. 30%, p = 0.451) by day three also did not differ significantly pre- and post-protocol implementation. The most common reasons for feed interruption were intubation/extubation and radiological procedures. Conclusion: Our current feeding protocol did not improve nutrient adequacy. The effectiveness of a more aggressive protocol in units where enteral nutrition is initiated within 24 hours should be investigated.